2019
DOI: 10.1002/bjs.11128
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of risk factors and complications associated with atrial fibrillation after oesophagectomy

Abstract: Background: Oesophagectomy is associated with high morbidity and mortality rates. New-onset atrial fibrillation (AF) is a frequent complication following oesophagectomy. Several studies have explored whether new-onset AF is associated with adverse events after oesophagectomy.Methods: This review was performed according to PRISMA guidelines. Eligible studies were identified through a search of PubMed, Scopus and Cochrane CENTRAL databases up to 25 November 2018. A meta-analysis was conducted with the use of ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 76 publications
(80 reference statements)
1
35
0
1
Order By: Relevance
“…Besides the abovementioned factors, age may play a major role in postoperative morbidity as older patients have more comorbidities and a reduced physiological resilience [25]. For example, older individuals have a higher probability of new-onset atrial fibrillation after esophagectomy [26], which is a known risk factor for pneumonia and AL. In addition, in patients ≥ 75 years, the nutritional status is often impaired [27] and the sarcopenia rate is higher [28,29].…”
Section: Patient Selection and Preparationmentioning
confidence: 99%
“…Besides the abovementioned factors, age may play a major role in postoperative morbidity as older patients have more comorbidities and a reduced physiological resilience [25]. For example, older individuals have a higher probability of new-onset atrial fibrillation after esophagectomy [26], which is a known risk factor for pneumonia and AL. In addition, in patients ≥ 75 years, the nutritional status is often impaired [27] and the sarcopenia rate is higher [28,29].…”
Section: Patient Selection and Preparationmentioning
confidence: 99%
“…Furthermore, patients receiving neoadjuvant chemotherapy also demonstrated more postoperative complications and greater impact on cardiopulmonary function, 14,30) which, in turn, reduced tissue perfusion and increased the risk of poor anastomotic healing. More risk factors for CAL after esophagectomy have been identified, which included diabetes mellitus, 2,6,20) BMI, 1) arrhythmia, 2,6,19,21) and smoker at diagnosis. 6) However, these factors were not identified in this study as no uniform conditions were followed.…”
Section: Discussionmentioning
confidence: 99%
“…2,4) Previous studies have identified various risk factors for CAL, such as neoadjuvant chemotherapy, 4,15,16) chronic obstructive pulmonary disease (COPD), 2) smoker at diagnosis, 6) pneumonia, 17,18) calcification of arteries, 9,19) diabetes mellitus, 2,6,20) body mass index (BMI), 1) and arrhythmia. 2,6,19,21) Some risk factors still remained controversial and so accurate prediction of risk groups for CAL remained very difficult. This study aimed to identify the risk factors of CAL after McKeown MIE via preoperative, intraoperative, and postoperative first day data and also offered the cutoff values.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hypertension was found to be associated with the occurrence of post-operative atrial fibrillation and could lead to arteriosclerosis. 29,30 Both atrial fibrillation and arteriosclerosis can compromise the blood supply to the site of the anastomosis, leading to anastomotic ischaemia and thus increasing the possibility of AL. 29 Mechanism of such phenomenon needs indepth research.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for this phenomenon may be that those patients initially identified with poor perfusion may have other risk factors of AL, which may influence the systemic tissue perfusion, such as coronary heart disease, hypertension and diabetes. For instance, hypertension was found to be associated with the occurrence of post‐operative atrial fibrillation and could lead to arteriosclerosis 0030. Both atrial fibrillation and arteriosclerosis can compromise the blood supply to the site of the anastomosis, leading to anastomotic ischaemia and thus increasing the possibility of AL 0029.…”
Section: Discussionmentioning
confidence: 99%